Analysis of traffic offload using multi‐attribute decision making technique in heterogeneous shared networks. Issue 4 (1st July 2019) - Sethuraman, Ramakrishnan; Kar, Subrat; Selvamuthu, Dharmaraja
Abstract : Over the years, the authors have witnessed tremendous growth in mobile data traffic. To address the capacity requirements, the mobile network operators (MNOs) are adding more radio nodes and spectrum layers. The spectrum layers vary in quality of service (QoS), utilisation and usage fee. To save operational costs, the MNOs could share their radio networks. The MNOs, therefore, should consider spectrum availability, link utilisation, link usage costs, traffic handling priorities and QoS for selecting the Donor link for traffic offload. In this study, the traffic offload scenario with multiple Donor links from different MNOs is analysed. The authors define the relevant queuing parameters for Donor link selection. Two hybrid multi‐attribute decision‐making (MADM) techniques, namely, (a) analytical hierarchical process (AHP) with grey relational analysis (GRA) technique and (b) entropy with range of values (RoV) technique for dynamic Donor link selection in traffic offload scenario and assess their benefits were compared. The authors use IP network measurements to derive the packet service time. It is observed that both the techniques Entropy‐RoV and AHP‐GRA align well with the dynamism of the network, though Entropy‐RoV method performed without any pre‐configuration. The AHP‐GRA technique requires pre‐configuration of parameters and when configured suitably, it can perform as a load equalisation technique.